Thiamine status of whitefish (Coregonus maraena) in the Baltic Sea - Marc M. Hauber; Oscar Nordahl; Vittoria Todisco; Emil Fridolfsson; Petter Tibblin; Samuel Hylander (PLoS ONE, 2026)
Many coregonine species have declined drastically across the Northern Hemisphere, including populations of Coregonus maraena (whitefish) in the Baltic Sea, and the mechanisms leading to these declines are not well investigated. An abrupt population crash occurred in the 1990s, coinciding with heavy declines in salmonid recruitment, also known as thiamine deficiency syndrome. Thiamine, i.e., vitamin B1, is an essential micronutrient needed for a functional metabolism. Offspring with thiamine deficiency have a high mortality posing significant negative impact on populations. Here, we aim to determine if whitefish, like other salmonids in the Baltic Sea, is affected by thiamine deficiency. Anadromous whitefish were therefore sampled during spawning in rivers of Southeastern Sweden, and we compared tissue concentrations and thiamine-dependent enzyme latencies to published thresholds. Further, we tested whether the variation in thiamine concentrations among individuals could be explained by physiological and morphological traits. Results showed that latency of thiamine-dependent enzymes along with egg thiamine concentrations suggest no evident thiamine deficiency. Concentrations were generally higher in the liver compared to muscle tissues. While females had lower liver thiamine concentrations compared to males, the opposite was found for muscle tissues, suggesting sex-specific patterns of allocation of the vitamin. Concentrations in eggs were positively related to the condition of the females and, similar to muscle and liver tissues, tended to be negatively related to standardized gill raker length. The latter is often used as a proxy for characterizing the feeding niche of coregonines. As has been observed in a number of other organisms (e.g., fish and molluscs), there was a reduction in thiamine concentration with length. Hence, the populations studied here showed no evidence of exhibiting thiamine deficiency. The variation in thiamine concentrations could largely be attributed to intrinsic physiological traits as well as traits associated with coregonine feeding niche.